In and Out of Place: Geographies of Revolt in Camus's La Peste - Erin Tremblay Ponnou-Delaffon (Studies in 20th & 21st Century Literature, 2015)
From Roland Barthes to Shoshana Felman, some of the most insightful readings of Albert Camus’s La Peste (The Plague) have focused on its historical dimension. In contrast, this article attends to less studied spatial representations, bringing recent insights from human geography to bear on depictions of Oran and exile in the novel. From its start, The Plague insistently connects plot, spatial setting, and notions of normativity and transgression. Understandings of place—and in particular, who or what is out of place—catalyze contestation and shape Camus’s universalized ethics of revolt, one that views evil and suffering as always out of place in a just world. Ultimately, this analysis suggests that places constitute not merely settings, sites, and objects in the Camusian imaginary, but a dynamic way of encountering and reading the world.
Keywords: Albert Camus; plague; place; space; Oran; ethics; evil; exile; revolt; La Peste